2013
DOI: 10.1089/sur.2012.042
|View full text |Cite
|
Sign up to set email alerts
|

Value of C-Reactive Protein in the Assessment of Organ-Space Surgical Site Infections after Elective Open and Laparoscopic Colorectal Surgery

Abstract: In patients with CRP <120.66 mg/L on post-operative day 5 or a decay from post-operative day two to five of >40%-48% in OPEN and LAP, respectively, OSI may be ruled out and the patient discharged safely. Careful workup is needed in those patients with higher postoperative CRP concentrations or lower apparent decay values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Even though the overall applicability of the included studies was good, the majority of patients underwent open surgery. The cut‐off values recommended by this meta‐analysis may be less applicable to laparoscopic surgery, which has been shown in some studies to result in lower levels of CRP and proinflammatory cytokines compared with open surgery. Moreover, the included studies did not distinguish between colonic and rectal resection, which may also lead to different postoperative inflammatory responses.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Even though the overall applicability of the included studies was good, the majority of patients underwent open surgery. The cut‐off values recommended by this meta‐analysis may be less applicable to laparoscopic surgery, which has been shown in some studies to result in lower levels of CRP and proinflammatory cytokines compared with open surgery. Moreover, the included studies did not distinguish between colonic and rectal resection, which may also lead to different postoperative inflammatory responses.…”
Section: Discussionmentioning
confidence: 95%
“…Seven studies met the inclusion criteria and had sufficient data to be included in the meta‐analysis. Of the most relevant studies that were excluded, one evaluated organ‐space surgical‐site infection rather than leaks specifically, six evaluated infectious complications overall with no subset analysis of leakage, and three did not carry out a predictive analysis for CRP and anastomotic leak.…”
Section: Resultsmentioning
confidence: 99%
“…Recently published articles have reported that laparoscopy-assisted surgery results in lower concentrations of CRP and proinflammatory cytokines than open surgery. 11 , 12 , 24 Therefore, it may be important to investigate the diagnostic accuracy of CRP concentrations for complications after laparoscopy-assisted and open surgery separately.…”
Section: Discussionmentioning
confidence: 99%
“…This fact enhances the interest of absolute values over tendencies, as it has already been stated in previous works having explored the interest of thresholds and that of decrements. 25,26 It is well established that most postoperative infections become clinically evident beyond POD 5, with advanced IAI. CRP was more accurate than PCT, as it was the case in several previous smaller series.…”
Section: Table 2 Daily Levels (Medians and Interquartilic Ranges) Ofmentioning
confidence: 99%